Penggunaan Artificial Intelligence (AI) bagi Pengajar guna Meningkatkan Efektivitas Pembelajaran di dalam Kelas - Prasetyo, Syahna Adityas; Aisyah, Nur; Novitasari, Sherly Eka; Afaf, Khansa Fadhilah; Firdausi, Arikah Atsiilatul; Firdauzi, Azzahra Zifa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the use of Artificial Intelligence (AI) by teachers in improving the effectiveness of classroom learning through literature review methods. Data was collected from various national and international journals using Google Scholar, SINTA, DOAJ and Garuda. The results show that AI has great potential to support learning through the provision of adaptive materials, rapid feedback, automation of routine tasks, personalization of learning, and increased student engagement. Various platforms such as Eduaide.ai, ChatGPT, and Google Classroom proved to provide significant support in the planning, implementation, and evaluation of learning. However, the main challenges found include low teacher literacy, limited infrastructure, technology access gaps, and ethical and privacy issues that are considered. This research confirms that AI does not replace the role of teachers, but becomes a strategic tool to create learning that is more effective, interactive, and relevant to the needs of the 21st century.